Buying into fair trade : - Keith R. Brown. (New York University Press, 2013)
This chapter highlights the ways that socially responsible markets have been detached from issues of morality. A fascinating account of how consumers first learn about, understand, and sometimes ignore the ethical implications of shopping, Buying into Fair Trade sheds new light on the potential for the fair trade market to reshape the world into a more socially-just place.